(untitled) (The Peerian Journal, 2025)
This article provides extensive information about the history of old Termiz. The periods of the stage stage are widely covered, and the development progress of the types of culture, art, and handicrafts is commented on. At the same time, the scientific conclusions of archaeologists, ethnographers, and local scientists who studied the history of Old Termiz are presented